2017
DOI: 10.1007/s10616-017-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultraviolet ozone treatment process for improvement of polycaprolactone (PCL) microcarrier performance

Abstract: Growing cells on microcarriers may have overcome the limitation of conventional cell culture system. However, the surface functionality of certain polymeric microcarriers for effective cell attachment and growth remains a challenge. Polycaprolactone (PCL), a biodegradable polymer has received considerable attention due to its good mechanical properties and degradation rate. The drawback is the non-polar hydrocarbon moiety which makes it not readily suitable for cell attachment. This report concerns the modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Bone tissue engineering, which shows great potential in developing bone grafts to induce bone tissue regeneration, has thus attracted considerable attention. Cell microcarriers composed of biodegradable polymers, such as poly (lactide) (PLA), polycaprolactone (PCL) and poly (lactide-co-glycolide) (PLGA), are among the most effective candidates due to their unique properties for bone tissue regeneration 5 7 . Furthermore, the main advantage of biodegradable microcarriers is that they provide a large number of cells for the field of cell therapy and can be administered using 10 to 16-gauge needles at the bone defect site 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Bone tissue engineering, which shows great potential in developing bone grafts to induce bone tissue regeneration, has thus attracted considerable attention. Cell microcarriers composed of biodegradable polymers, such as poly (lactide) (PLA), polycaprolactone (PCL) and poly (lactide-co-glycolide) (PLGA), are among the most effective candidates due to their unique properties for bone tissue regeneration 5 7 . Furthermore, the main advantage of biodegradable microcarriers is that they provide a large number of cells for the field of cell therapy and can be administered using 10 to 16-gauge needles at the bone defect site 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The ATR-FTIR spectra ( Figure 4 a) of untreated and O 3 -treated scaffolds featured typical peaks for PCL: 2943 cm −1 asymmetric CH 2 stretching; 2865 cm −1 symmetric CH 2 stretching; 1721 cm −1 carbonyl (C=O) stretching; 1294 cm −1 C–O and C–C stretching in the crystalline phase; 1159 cm −1 C–O and C–C stretching in the amorphous phase; 1241 cm −1 asymmetric C–O–C stretching; 1185 cm −1 OC–O stretching. Such spectra have been registered in earlier studies [ 42 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Major peaks in untreated (0 min) pollen were assigned from previous FTIR studies on sporopollenin, with peak attributions being hydroxyl (3300 cm −1 ), aliphatic (2925 cm −1 ), carbonyl (1670 cm −1 ) aromatics (1515 cm −1 , 1425 cm −1 ), and COR (1028 cm −1 ) ( Figure a and Figure S7a, Supporting Information) . Subtracting UV–O treated spectra from untreated spectra suggested reductions in absorption for most major peaks of interest, and highlighted a relatively large increase in the shoulder peak at 1718 cm −1 (Figure b), which may be attributed to CO and correlates to the increased R 2 CO binding observed from the XPS analysis.…”
Section: Resultsmentioning
confidence: 87%
“…However, ultraviolet–ozone (UV–O) treatment is a more easily implementable surface modification process, which also leads to improved surface wetting of polymers, and potential enhancements in polymer/cell adhesion . Studies with polymer microparticles have shown UV–O treatment to easily and successfully modify the chemistry and interfacial properties of polystyrene and polycaprolactone microparticles leading to improved wetting, particle self‐assembly, polymer binding, and particle/cell adhesion …”
Section: Introductionmentioning
confidence: 99%